2010
DOI: 10.1002/cncy.20059
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cysts

Abstract: Preoperative diagnosis of pancreatic cysts benefits from integrating the clinical, radiological, and cytological features. As patient management algorithms evolve to increasingly nonsurgical options, accuracy in distinguishing mucinous from nonmucinous and benign from malignant mucinous cysts is important. This review focuses on pseudocysts, serous cystadenomas, intraductal papillary mucinous neoplasms (IPMNs), and mucinous cystic neoplasms. Patients with pseudocysts almost always present with pancreatitis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(33 citation statements)
references
References 83 publications
0
33
0
Order By: Relevance
“…For example, the diagnostic value of the tumor-specific antigens secreted by the neoplastic epithelium, such as carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 and cancer antigen 125, has been analyzed in numerous studies [42,43,44,45]. Of these, cyst fluid CEA appears to have the most promising performance criteria so far in distinguishing mucinous from nonmucinous cystic lesions of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the diagnostic value of the tumor-specific antigens secreted by the neoplastic epithelium, such as carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 and cancer antigen 125, has been analyzed in numerous studies [42,43,44,45]. Of these, cyst fluid CEA appears to have the most promising performance criteria so far in distinguishing mucinous from nonmucinous cystic lesions of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to imaging, aspiration of cyst fluid contents can be conveniently and safely performed by EUS-guided fine-needle aspiration, which provides material for cytopathology and the assessment of tumor markers. Unfortunately cystic lesions, in general, are fairly hypocellular, such that the sensitivity of cytology examination remains low (∼50%) despite a high specificity [20,21,22]. Thus, there is an unmet need for ancillary biomarkers in cyst fluid material that can provide additional and reliable distinction between mucinous cystic precursors of pancreatic cancer versus clinically insignificant nonmucinous lesions.…”
Section: Introductionmentioning
confidence: 99%
“…In cases with scant cellularity or small volume of aspirated fluid, it has been reported that molecular analyses (Kras mutation, more than two LOH) are supportive of the diagnosis of neoplastic (mucinous) cystic lesion. 9 Other low-grade mucinous cystic neoplasms (MCN) usually have scant cellularity and single cells or small clusters of cells with basally placed nuclei and cytoplasmic mucin. A recently described mucinous non-neoplastic cyst (MNC), not a well-recognized entity, also shares many clinical and radiological features with MCN and IPMN and may resemble BGH.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Cyst fluid may contain acute and chronic inflammatory cells, histiocytes, and macrophages. [20] Only complicated cases with gastrointestinal epithelial and mucin contamination, particularly from the stomach, should include cystic lining epithelial cells. [19,21,22] Van der Waaij et al analyzed 12 studies and demonstrated that CEA levels below 5 ng/mL present a specificity of 95% for pseudocyst formation.…”
Section: Discussionmentioning
confidence: 99%